Meritve površinske erozije tal v gozdu Slovenske Istre - Zorn, Matija (Gozdarski vestnik, 2010)
In order to assess protection role of forests we performed measurements of interrill soil erosion under three different land uses in Slovenian Istria between 2005 and 2008, namely on bare soils in a young olive grove, on a grassland under overgrowth, and in a forest. The measurements were performed south of the village of Marezige in the Rokava River catchment on eight close derosion plots of 1 m2 area. In the first year of measurements (May 2005 through April 2006), soil loss due to the surface erosion on bare soils in the olive grove with the slope of 5.5? amounted to 9013 g/m2 (90 t/ha), on the grassland under overgrowth with the slope of 9.4? it amounted to 168 g/m2 (1.68 t/ha), in the forest with the slope of 7.8? it amounted to 391 g/m2 (3.91 t/ha), and in the forest with the slope of 21.4? it amounted to 415 g/m2(4.15 t/ha). These results show that soil detachment and soil erosion on natural land (forest, grassland under overgrowth) is much less ample compared to intensive agricultural use (olive grove). The measurements also showed that only a few large rainfall events caused the major part of the annual soil loss.
Keywords: pedogeografija; erozijski procesi; erozija prsti; Dragonja; Istra; Istria; Slovenia; Slovenija